Recent Advancements in Imaging of Oral Cancer (Indian Journal of Forensic Medicine & Toxicology, 2020)
In oral fissure, “squamous cell carcinoma (SCC) “is the commonest oral carcinomas which comprises (90-95%). After the 5th decade of age, male predilection is double as compared to females. (40%)of OSCCare confined to the dorsal or ventral surface ofthe tongue,(thirty percent)on the floor of the oral fissure.“OSCC” regularly distresses maxillary and mandibular attached gingiva, buccal mucosa, retro-molarandpalatal region. In 5 years’ survival percentage series from 20% OSCC in the floor of the mouth to 60%OSCC in alveolus portion of jawbone depicting poor prognosis. Although it is tough but it is required todo imaging studies to understand the results at the initialphases of the disease. Various modalities include{conventional plain film radiography, panoramic radiograph, cone beam computed tomography,Perfusioncomputed tomography,Magnetic resonance imaging–(diffusion-weighted MRI, dynamic contrast-enhancedMRI), ultrasonography, single-photon emission computed tomography}, fusion techniques such as (ECT/CT, CT/MRI, PET/CT, PET/MRI) along with nuclear medicines – (2-deoxy-2-[18F] fluoro-D-glucose),(18F-FDG), 18F-3-fluoroalpha-methyltyrosine, (18F-FAMT) and L-1-[11C]-tyrosine(C-tyrosine),radionuclide imaging. These various imaging diagnostic modalities support in the grading of the tumor,valuation of the vascular supply, resolution about metastasis combined with confined lymph nodes as wellas detached organs. Furthermore, imaging lessons help to forecast the possibility of resection and advancemanagement, graft establishment, and diversity amongst reactive and metastatic lymph nodes,and amongstdiseases reappearance and marks or adversative reactions of post-operation or emission therapy
Keywords: Oral squamous cell carcinoma, imaging modalities, radionuclide imaging.